Priorities for developing countries in the global response to non-communicable diseases - Maher Dermot; Ford Nathan; Unwin Nigel (BMC, 2012)
Abstract The growing global burden of non communicable diseases (NCDs) is now killing 36 million people each year and needs urgent and comprehensive action. This article provides an overview of key critical issues that need to be resolved to ensure that recent political commitments are translated into practical action. These include: (i) categorizing and prioritizing NCDs in order to inform donor funding commitments and priorities for intervention; (ii) finding the right balance between the relative importance of treatment and prevention to ensure that responses cover those at risk, and those who are already sick; (iii) defining the appropriate health systems response to address the needs of patients with diseases characterized by long duration and often slow progression; (iv) research needs, in particular translational research in the delivery of care; and (v) sustained funding to support the global NCD response.